Syntheses of Boron Nitride Nanotubes from Borazine and Decaborane Molecular Precursors by Catalytic Chemical Vapor Deposition with a Floating Nickel Catalyst - Chatterjee, Shahana; Kim, Myung Jong; Zakharov, Dmitri N.; Kim, Seung Min; Stach, Eric A.; Maruyama, Benji; Sneddon, Larry G. (AMER CHEMICAL SOC, 2012)
Multi- and double-walled boron nitride nanotubes (BNNTs) have been synthesized with the aid of a floating nickel catalyst via the catalytic chemical vapor deposition (CCVD) of either the amine-borane borazine (B3N3H6) or the polyhedral-borane decaborane (B10H14) molecular precursors in ammonia atmospheres. Both sets of BNNTs were crystalline with highly ordered structures. The BNNTs grown at 1200 degrees C from borazine were mainly double-walled, with lengths up to 0.2 mu m and similar to 2 nm diameters. The BNNTs grown at 1200-1300 degrees C from decaborane were double- and multiwalled, with the double-walled nanotubes having similar to 2 nm inner diameters and the multiwalled nanotubes (similar to 10 walls) having similar to 4-5 nm inner diameters and similar to 12-14 nm outer diameters. BNNTs grown from decaborane at 1300 degrees C were longer, averaging similar to 0.6 mu m, whereas those grown at 1200 degrees C had average lengths of similar to 0.2 mu m. The BNNTs were characterized using scanning and transmission electron microscopies (SEM and TEM), and electron energy loss spectroscopy (EELS). The floating catalyst method provides a catalytic and potentially scalable route to BNNTs with low defect density from safe and commercially available precursor compounds.
Keywords: BISCYCLOPENTADIENYL METAL-COMPOUNDS; CERAMIC CONVERSION REACTIONS; YIELD POLYMERIC PRECURSOR; WALLED CARBON NANOTUBES; LOW-TEMPERATURE GROWTH; ATOMIC STRUCTURES; BN NANOTUBES; LARGE-SCALE; PYROLYSIS; MECHANISM